Conscious and Correct Use of Biostatistical Methods in Medical Researches: From Planning to Reporting the Results - Part I. - KARABULUT, Erdem (Duzce Medical Journal, 2022)
The principles and methods of biostatistics serve as a guide for healthcare practitioners in both their daily and scientific work. Biostatistics principles and methods should be considered at every stage. A scientific research requires a multidisciplinary teamwork and each team must include a biostatistics expert at the planning stage of the study. During the planning phase, a biostatistics expert can answer all questions about the design, conduct, data processing, data analysis, presentation of the results, and publication of the results. Reporting guidelines for almost all research designs were developed to improve the quality and transparency of research reports. When the research results are presented in a structured and standardized way using these guidelines, it will allow the readers to interpret the findings more easily and accurately. It is now easier for researchers to gain access to a variety of software or web applications that allow them to perform basic and advanced statistical analyses. However, erroneous/misleading results are produced when these software are used unconsciously or incorrectly by those with insufficient statistical knowledge. Health professionals should also have sufficient statistical knowledge to identify errors in articles related to their field. Therefore, they are expected to have knowledge of research designs and basic statistical concepts. Knowing the basic concepts such as population, sample, sampling methods, random assignment of volunteers to groups, parameters, statistics, data types, etc. will help the readers while evaluating the material and method sections of the articles.